2020
DOI: 10.1016/j.jallcom.2019.153250
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure, cobalt and iron speciation and oxygen non-stoichiometry of La0.6Sr0.4Co1-yFeyO3-δ nanorods for IT-SOFC cathodes

Abstract: Single-phased La 0.6 Sr 0.4 Co 1-y Fe y O 3-d (y = 0.2, 0.5, 0.8) nanorods exhibiting the rhombohedral perovskite-type phase were synthesized by a pore-wetting technique. We studied their chemical composition, crystal and electronic structures, morphology and hyperfine properties as a function of the Co/Fe content of the samples. Our results demonstrate that Co cations exhibit a slightly lower oxidation state than Fe ones, resulting in a higher oxygen non-stoichiometry d for Co-rich samples. In addition, the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 34 publications
(49 reference statements)
0
5
0
Order By: Relevance
“… 133 Alternatively, one can use integrated descriptors and determine the energy where the integrated absorption reaches a certain fixed value. For example, Capehart et al suggested using as a descriptor of the absorption edge position an energy value corresponding to 80% of the integrated absorption spectrum area for the corresponding metal foil 134 , 135 ( Figure 6 a).…”
Section: From Spectra To Descriptors Of Electronic and Geometric Strumentioning
confidence: 99%
See 1 more Smart Citation
“… 133 Alternatively, one can use integrated descriptors and determine the energy where the integrated absorption reaches a certain fixed value. For example, Capehart et al suggested using as a descriptor of the absorption edge position an energy value corresponding to 80% of the integrated absorption spectrum area for the corresponding metal foil 134 , 135 ( Figure 6 a).…”
Section: From Spectra To Descriptors Of Electronic and Geometric Strumentioning
confidence: 99%
“…Frequently, information about the oxidation state can be easily extracted from the examination of the absorption edge position since a higher oxidation state is associated with a shift of the absorption edge toward larger energies. For example, a nearly linear relationship between the Co K-edge position and the Co oxidation state has been reported (Figure a). , Using XAS spectra for reference materials with known oxidation state, the relationship between the oxidation state and the edge position can be established and used to find the oxidation state of the new material of interest. It should be however noted that instead of a nominal oxidation state, in some cases the absorption edge position rather characterizes the so-called coordination charge, which accounts for charge redistribution due to chemical bonding. , …”
Section: From Descriptors To Physical Models Of Electrocatalyst Struc...mentioning
confidence: 99%
“…Early research included the examination of a few manganese oxide specimens [3][4][5] and the morphological examination of manganese oxides derived from various precursors [6][7][8]. Manganese oxide shows a variety of oxidation states (+2, +3, +4) and crystal forms, including MnO, MnO 2 , Mn 2 O 3 and Mn 3 O 4 , which contribute to their effective gas sensing capabilities [9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Mixed ionic and electronic conducting (MIEC) oxides have been considered as cathode materials because of their superior ORR activity at intermediate temperatures [ 12 , 13 , 14 ]. Many cobalt-containing MIEC oxides, such as La 0.6 Sr 0.4 CoO 3−δ , La 0.6 Sr 0.4 Co 0.2 Fe 0.8 O 3−δ , and Ba 0.5 Sr 0.5 Co 0.8 Fe 0.2 O 3−δ , have been used as cathode materials in IT-SOFCs [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%